(untitled) (Canadian Eye Care Today, 2022)
Many options now exist for patients seeking surgical correction of myopia. The challenge lies in selecting the right procedure for the right patient. This article provides an overview of current refractive surgery options and discusses the clinical and imaging considerations in decision-making.